Mechanical Properties of Welded Deformed Reinforcing Steel Bars - Ahmed, Ghafur H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2015)
Reinforcement strength, ductility and bendability properties are important components in design of reinforced concrete members, as the strength of any member comes mainly from reinforcement. Strain compatibility and plastic behaviors are mainly depending on reinforcement ductility. In construction practice, often welding of the bars is required. Welding of reinforcement is an instant solution in many cases, whereas welding is not a routine connection process. Welding will cause deficiencies in reinforcement bars, metallurgical changes and re-crystallization of microstructure of particles. Weld metal toughness is extremely sensitive to the welding heat input that decreases both of its strength and ductility. For determining the effects of welding in reinforcement properties, 48 specimens were tested with 5 different bar diameters, divided into six groups. Investigated parameters were: properties of un-welded bars; strength, ductility and density of weld metal; strength and ductility reduction due to heat input for bundled bars and transverse bars; welding effect on bars’ bending properties; behavior of different joint types; properties of three weld groove shapes also the locations and types of failures sections. Results show that, strength and elongation of the welded bars decreased by (10-40%) and (30-60%) respectively. Cold bending of welded bars and groove welds shall be prevented.